2021
DOI: 10.1177/10760296211010241
|View full text |Cite
|
Sign up to set email alerts
|

Blood Urea Nitrogen to Serum Albumin Ratio Independently Predicts Mortality in Critically Ill Patients With Acute Pulmonary Embolism

Abstract: Acute pulmonary embolism (APE) is one of the prominent causes of death in patients with cardiovascular disease. Currently, reliable biomarkers to predict the prognosis of patients with APE are limited. The present study aimed to investigate the association of blood urea nitrogen to serum albumin (B/A) ratio and intensive care unit (ICU) mortality in critically ill patients with APE. A retrospective cohort study was performed using data extracted from a freely accessible critical care database (MIMIC-III). Adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Using the data extracted from MIMIC-III, Fang et al investigated the correlation between BAR and prognosis of 1048 ICU patients with acute pulmonary embolism and concluded that BAR was an independent predictor for ICU mortality as well as 28-day mortality after ICU admission and the predictive performance of BAR was superior to the SOFA score and APSIII score. 30 Moreover, Huang et al conducted a retrospective, observational study of 602 patients and demonstrated that elevated BAR at admission is an independent risk factor for in-hospital mortality in coronavirus disease patients (2019). 31 Our study added the evidence that BAR was a reliable predictor for prognosis of patients with disease of the respiratory system.…”
Section: Discussionmentioning
confidence: 99%
“…Using the data extracted from MIMIC-III, Fang et al investigated the correlation between BAR and prognosis of 1048 ICU patients with acute pulmonary embolism and concluded that BAR was an independent predictor for ICU mortality as well as 28-day mortality after ICU admission and the predictive performance of BAR was superior to the SOFA score and APSIII score. 30 Moreover, Huang et al conducted a retrospective, observational study of 602 patients and demonstrated that elevated BAR at admission is an independent risk factor for in-hospital mortality in coronavirus disease patients (2019). 31 Our study added the evidence that BAR was a reliable predictor for prognosis of patients with disease of the respiratory system.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Blood urea nitrogen to serum albumin ratio (BAR) is a novel prognostic biomarker discovered in recent years, which combines two important predictors-urea nitrogen and albumin, and this biomarker shows a good predictive effect in the mortality of patients with pneumonia or acute pulmonary embolism. [10][11][12][13][14] Most critically ill patients admitted to the intensive care unit (ICU) have multiple organ damages. Chronic heart failure is a common comorbidity, which makes the mortality rate of these patients higher.…”
Section: Introductionmentioning
confidence: 99%
“…For aspiration pneumonia patients, Ryu et al [ 27 ]demonstrated that the BUN/ALB ratio was associated with increased 28-day mortality. In addition, Fang et al [ 28 ]concluded that the BUN/ALB ratio could be a useful prognostic tool to predict mortality in critically ill patients with an acute pulmonary embolism. In our prospective cohort study, we first investigated the association between BUN/ALB ratio and in-hospital and 90-day all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%